ANALISIS BIAYA UNTUK PENGAMBILAN KEPUTUSAN BISNIS - Sumadji Harryono (UMSurabaya Publishing, 2011)
Cost analysis plays an important role in managerial economics because basically every managerial decision requires a comparison between the costs and benefits. In this paper we will discuss the concept of cost of production, how to minimize cost, short-term cost analysis, and long-term as well as the relationship between the two. Next we will discuss the shift in cost curves, learning curve, and the application fee in the company. This cost analysis will then be used as ingredients in subsequent management processes, especially in the context of profit maximization.Â Key-words: cost analysis, managerial economics, managerial decision.